Association of Night Hypoxia with Otolith Dysfunction Patients Having Obstructive Sleep Apnea - Zafar Mahmood, Hammad Raza, Ikram Ullah, Salman Niaz Ahmed, Sohail Tirmizi, Saad Shakil (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find the association of night hypoxia with otolith dysfunction patients having obstructive sleep apnea. Study design: Prospective study Place and duration of study: Department of ENT and Head & Neck Surgery, Liaquat College of Medicine & Dentistry, Karachi from 1st January 2021 to 30th September 2021. Methodology: Fifty cases underwent polysomnography (PSG) for diagnostic purposes in context to suspicion of the night hypoxia were enrolled. Analysis for PSG was based on the variables as apnea hypopnea indexing, minimal level of oxygen of saturation, average level of oxygen-saturation, time of sleep as well as 3-4% de-oxygen saturation-indices. The vestibular-function test was performed by including vHIT and cVEMP as well as ocular VEMPs. Head impulses in horizontal method were used for quantitative assessment of the vestibular ocular reflexes. Results: Mean age of the study participants was 50.9±10.9 years. Age and body mass index of the participants were not significantly differed from obstructive sleep patients. Male gender appeared to be prominent in gender distribution. Incidence of hypertension and diabetes especially appeared to be higher in patients who had AHI ≥15. Conclusion: No considerable association was found between sleep apnea and vestibular function.